BUKU ESAI FOTOGRAFI “SINAR HARAPAN DI BUKIT GREEN VILLAGE“ UNTUK MENGOPTIMALKAN OBYEK WISATA FLYING FOX GEDANGSARI GUNUNG KIDUL YOGYAKARTA - Puji Handayani Putri (Jurnal Dinamika Informatika, 2019)
Abstract Gedangsari Subdistrict in Gunungkidul is the sub-district which is the northernmost and directly borders with Kecamatan Bayat, Klaten Regency, Central Java. In Gedangsari sub-district it has beautiful natural potential and is still natural and beautiful, one of which is Green Village. Green Village has the longest Flying Fox attraction in Southeast Asia. But unfortunately the lack of publications makes the tourism potential less known to the public. So there needs to be an effort to optimize the tourism potential to be known by the community. One of the authors' efforts is to design a photographic essay book entitled "Sinar Harapan in the Green Village Hill" with the intention of providing an overview of the life of tourist managers and the community around tourism objects. With this photography essay book, it is expected that more tourists visiting will not only be on vacation but can also contribute constructive creative ideas. The analytical method used is qualitative descriptive analysis. Data collection is done by literature study, in-depth interviews and observations. The output is in the form of a Flying Fox photography essay book, bookmark, poster. The camera used is the Professional Nikon D3300 DSLR camera. Keywords: essay books, photography, Flying Fox attractions